Short-term Outcomes of Ambulatory Colectomy for 157 Consecutive Patients. Issue 2 (August 2019) - Gignoux, Benoit; Gosgnach, Marilyn; Lanz, Thomas; Vulliez, Alexandre; Blanchet, Marie-Cecile; Frering, Vincent; Faucheron, Jean-Luc; Chasserant, Philippe
Abstract : Objective: To evaluate short-term outcomes of laparoscopic colectomy for selected consecutive patients in an ambulatory setting at two institutions. Background: Several studies showed that an enhanced recovery protocol for colorectal surgery reduces postoperative morbidity and mortality, and shortens the length of hospital stay. The development of such a program has allowed us to gradually reduce the length of stay for colorectal surgery, until ambulatory management. Methods: Between February, 2013 and December, 2016, all patients scheduled for elective laparoscopic colectomy and meeting rigorous criteria for ambulatory surgery were included. Outcome was prospectively studied. Results: One hundred fifty-seven patients (70 women) with a median age of 61 years (range 25–82 years) were included. The ambulatory rate for colectomy was 30.5%. Median operative time and length of in-hospital stay were 95 minutes (range 45–232 minutes) and 10.0 hours (range 7–14.7 hours), respectively. The admission rate was 7.0% due to operative difficulties (4 patients), medical reasons (4 patients), and social reasons (3 patients). Outcomes for these patients were uneventful and the median length of hospital stay was 3.1 days (range 1–14 days). An unscheduled consultation was necessary for 30 patients (20.5%). Nine patients required readmission (6.1%), of whom 6 required reoperation (3.8%). The overall 30-day morbidity rate was 24.8%. The mortality rate was 0%. Conclusions: This is the first case of consecutive patients undergoing ambulatory colectomy for malignant or benign disease. We demonstrated the feasibility, safety, and reproducibility of outpatient colectomy for selected patients. In our experience, 30% of patients scheduled for elective colectomy can be managed in an ambulatory setting.